Juvenile Dermatomyositis: An Update (Bangladesh Journal of Child Health, 2010)
Juvenile idiopathic inflammatory myopathies (JIIM) are rare conditions which are probably autoimmune in nature. Childhood myositis is relatively more homogeneous than adult myositis. Juvenile dermatomyositis (JDM) is the most common paediatric inflammatory myopathy. It is a systemic vasculopathy with characteristic cutaneous findings and focal areas of myositis resulting in progressive proximal muscle weakness. Other paediatric inflammatory myopathies are: fewer cases of polymyositis, amyopathic dermatomyositis, overlap myositis and inclusion body myositis.JDM is a multi-system disease of uncertain aetiology that results in non-suppurative inflammation of striated muscles and skin. It differs from the adult form of dermatomyositis by much higher incidence of vasculitis, often with intimal proliferation of small blood vessels, thrombosis, and sometimes infarction, which can involve gastrointestinal tract and myocardium as well. Early in the course it is characterized by immune complex vasculitis of varying severity and later by development of calcinosis.  DOI: 10.3329/bjch.v33i2.5684  Bangladesh Journal of Child Health 2009; Vol.33(2): 59-65